Uso de inoculante microbiano e farelo de arroz na ensilagem de capim-mombaça - Carvalho, Ana Paula da Silva (2017)
The forage shortage during the dry season compromises the feeding of ruminants, which requires forage production and storage alternatives, such as the silage technique, that allows animal feeding at this time of year. This technique consists in the preservation of forage in anaerobic environment, through the fermentation of soluble sugars, by the anaerobic epiphytic microorganisms of the plant, in organic acids, mainly lactic acid, which reduces the pH values. However, tropical grasses do not present adequate contents of dry matter and soluble carbohydrates for the efficient fermentation process, making necessary the use of additives for desirable fermentation. The goal was to evaluate the influence of rice bran and bacterial additive (homolactic bacteria) on fermentative characteristics, nutritive value and kinetic parameters in Mombaça guineagrass silages. The experimental design was completely randomized, with three replications. The treatments corresponded to a 4 x 5 factorial, with four additive (control, bacterial additive, rice bran, bacterial additive and rice bran) and five silos opening times (0, 3, 7, 14 and 21 days after closure). With the collected samples, analyzes of chemical characteristics, pH and kinetic parameters of the silage were carried out. At both farms, the fiber content decreased, while the crude protein contents increased with the use of rice bran with or without the bacterial additive in Mombaça guineagrass silage. Regarding the kinetic parameters, the silages with rice bran showed less digestion rate and lag time in the two farms. At one farm, the use of the additives, both alone and in combination, promoted the decrease of pH in comparison to the in-natura Mombaça guineagrass, and for N-ammoniacal, no treatment was presented levels above the maximum limit of 12%. The rice bran improved the fermentative and chemical characteristics of the produced silages, while the use of bacterial additive assisted in the fermentation during the ensiling of Mombasa guineagrass.